The qRT-PCR in A Nasal Swab Leprosy Patient’s at Dr. M. Djamil Padang Hospital - Ariani, Tutty; Asri, Ennesta; Putra, Andani Eka (GoAcademica Research & Publishing, 2024)
Leprosy, caused by Mycobacterium leprae, in 2016, Indonesia reported 16,826 new leprosy cases, with a prevalence rate of 0.71 per 10,000 individuals and a new case detection rate of 6.5 per 10,000 individuals. This study describes the result of a quantitative real-time polymerase chain reaction (qRT-PCR) in the nasal mucosa smear of a leprosy patient at the Dermatology and Venereology Polyclinic of Dr. M. Djamil Padang Hospital. This study adopts an observational approach with a width cut design, specifically employing a cross-sectional study methodology on leprosy patient at the Dermatology and Venereology Polyclinic of Dr. M. Djamil Padang Hospital, Indonesia between February 2023 until February 2024. The qRT-PCR quantity value of nasal mucous discharge is analyzed by a real-time PCR machine. The provided data presents characteristics of a sample population (N = 36) with leprosy. The majority of the leprosy-affected individuals in this study are between 8 and 68 years old, with a median age of 34. According to the World Health Organization (WHO) classification indicates that 83.33% of cases are multibacillary (MB). A combination RLEP/ qRT-PCR assay was developed to enable laboratory-based care and follow-up of leprosy patients attending our outpatient polyclinic in M. Djamil, Padang. The assay offers a sensitive and precise method for assessing the bacterial load and viability of M. leprae from nasal swab samples. It can be used for treatment response monitoring and early diagnosis.